(untitled) (Journal of Comparative Social Work, 2015)
This paper presents preliminary research about the process of the construction of concepts in social work. In this case, it is referred to as a social worker’s construction of “family” as a concept and as a field of practice in a current Cuban context. Based on an exploratory and qualitative research design, the paper presents an analysis that also opens to the discussion about social work with families in Cuba. The findings shows that Cuban social workers think of family as a group with cohabitation and affinity, which is more important than consanguinity, as a dimension for family definitions. They also point at structures of family, special bonds in family network and the social internal and external functions of family in their definitions. Among these functions, the transmission of cultural values, as well as the emotional support and shelter for members, seems relevant. Regarding family as a field of practice, they all share the criteria that is necessary for practice to develop a contextual analysis of each situation that goes from macro-contextual aspects to the micro-reality of family. The importance of structural matters and their impact on family functions is also a common idea, which is nucleated around a multigenerational reality of Cuban families and evaluated as a positive or negative impact depending on the case in question. They consider social work with families, and social work in general, to be in a critical situation in relation to losing professionalization and social recognition. The reasons explaining these ideas have to do with the instability of social work institutionalization and the recent retraction of social services. These variations have obeyed the changes in a Cuban context that affects the entire welfare system and social work’s position in it.